Developing a quality and safety assessment framework for Iran's military hospitals - Nader Markazi-Moghaddam; Mojgan Mohammadimehr; Mahdi Nikoomanesh; Ramin Rezapour; Sanaz Zargar Balaye Jame (BMC, 2024)
Abstract Background The first crucial step towards military hospitals performance improvement is to develop a local and scientific tool to assess quality and safety based on the context and aims of military hospitals. This study introduces a Quality and Safety Assessment Framework (Q&SAF) for Iran's military hospitals. Methods This is a literature review which continued with a qualitative study. The Q&SAF for Iran's military hospitals was developed initially, through a review of the WHO's framework for hospital performance, literature review (other related framework), review of military hospital-related local documents, consultations with a national and sub-national expert. Finally, the Delphi technique used to finalize the framework. Results Based on the literature review results; 13 hospital Q&SAF were identified. After reviewing literature review results and expert opinions; Iran's military hospitals Q&SAF was developed with 58 indictors in five dimensions including clinical effectiveness, safety, efficiency, patient-centeredness, and Responsive Management (Command and Control). The efficiency dimension had the highest number of indictors (19 indictors), whereas the patient-centered dimension had the lowest number of indices (4 indictors). Conclusion Regarding the comprehensiveness of the developed assessment framework due to its focus on the majority of quality dimensions and important components of the hospital's performance, it can be used as a useful tool for assessing and continuously improving the quality of hospitals, particularly military hospitals.